Occupational Stress And Individual Well Being Of Nepal Police Officials - Gwachha, Anju (Khwopa Journal, 2023)
Stress at workplace is one of the emerging issues in various profession. The perceived level of stress has an adverse effect in job performance and well-being of employees. The policing is considered as very stressful occupation. The present study entitled, ‘occupational stress and individual well-being of Nepal police official’ was undertaken to examine the effect of perceived stress on individual well-being of Nepal Police Officials. The survey was done through administration of the structured questionnaire to different categories and levels of police working in Kathmandu valley. Descriptive statistics, correlation and hierarchical regression were used to analyze the collected data. The study results significant influence of perceived occupational stress on individual well-being. The findings suggests that organization, management, and employees should emphasis on stress management approaches for increasing effectiveness and efficiency of organization as the individual well-being is foremost requirements.